Electronic structure, optical and thermal/concentration quenching properties of Lu2−2xEu2xWO6 (0 ≤ x ≤0.2). (October 2015) - Chen, Xiang-Yang; Zhang, Zhi-Jun; Feng, Ang; Xu, Meng; Zhao, Jing-Tai; Xu, Fang-Fang
Graphical abstract: Highlights: The band gap of Lu2 WO6 is calculated to be 3.13 eV using the CASTEP mode. Valent state and occupation site of Eu are clarified by X-ray absorption fine structure (XAFS) spectra. The thermal/concentration quenching mechanisms of Eu in Lu2 WO6 have been investigated in detail. Abstract: Density functional theory calculations on monoclinic Lu2 WO6 is carried out using the Cambridge Sequential Total Energy Package code. The result indicates that Lu2 WO6 is a broad band gap semiconductor with an indirect band gap of 3.13 eV. Eu ions are trivalency and the average coordination number is 7.6(5), indicating that the site of Lu is occupied by Eu. The activation energy Δ E is calculated as 0.314 eV. In addiation, the thermal quenching mechnism of Eu-activated Lu2 WO6 and the different concentration quenching mechanisms for 5 D0 and 5 D1 emissions of Eu ions have been proposed.